Implementasi Peningkatan Minat Berliterasi, Numerasi Dan Adaptasi Teknologi Siswa Melalui Program Kampus Mengajar Di SD Negeri 13 Padang Lampe - Nurul Auliah. NM; Muhammad Syukur (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Education is one of the important things in human life. Where this indicates that every human being has the right to get a proper education and is also expected to develop in it. In general, education means a process in life to develop oneself in order to live life in the future. The role of education is very large in preparing and developing each individual to be able to compete with other individuals. In undergoing the learning process at school and at home, strengthening literacy and numeracy as well as technological adaptation is very important to do because this is one of the main things that can support and improve the quality of society.